Proactive stakeholder management in the port planning process: empirical evidence from the Port of Brussels - Michael Dooms; Cathy Macharis; Alain Verbeke (European Regional Science Association (ERSA), 2004)
Port planning and port management are increasingly influenced by a variety of external stakeholders, each pursuing specific strategic objectives with regard to port activities and port development. A greater focus on external stakeholders may increase the port activities' legitimacy at the city and regional levels, and may also contribute to sustainable development. In this paper, a new port planning methodology is designed within the context of the development of the Port of Brussels (Belgium) Master plan, time horizon 2015. This new planning methodology describes the port planning process, building upon the decomposition of the total port area in several distinct port objectives were taken into account in this planning process, and how this multi-zone, multi-stakeholder approach can be generalized to improve upon conventional strategic port planning processes. Keywords: Port planning, stakeholder management, evaluation methods
Keywords: 330; Port planning; stakeholder management; evaluation methods